Possibilidades de exploração da história da ciência na formação do professor de matemática: mobilizando saberes a partir da obra de Nicolau Copérnico de revolutionibus orbium coelestium - Mendes, Maria José de Freitas (2010)
This study aims to analyze the implications that the knowledge of an important work for the History of Science, De revolutionibus orbium coelestium , by Nicholas Copernicus, can bring for the formation of Mathematics professors. The study focuses on Book I of Copernicus s work, where, in the final part, is found the Table of the Subtense Straight Lines in a Circle, a true sine table constructed by the author. The study considers two theoretical references, the History of Science and of Mathematics, in the professor s formation searched amongst others in Miguel and Miorm, Brito, Neves and Martins, and Radford, and the necessary teaching knowledge professors mst have, on the basis of Gauthier, Schulman and Imbernón amongst others, through which it is established a net of knowledge grouped in dimensions such as mathematical, psycho pedagogical, cultural and practical diversity, that guide the study analysis. In the search for more necessary elements to enrich the analysis, beyond the theoretical research in Book I, it is carried through, with under graduation pupils, future Math professors, the construction of a sine table following the project used in De revolutionibus . The study still makes a description of the life and work of Nicholas Copernicus, detaching the historical context where the author lived and the conceptions about the Universe existing at that time. The research reveals that the studied work is an important source of culture, able to provide to the Mathematics professor in formation, beyond the conceptual and procedural mathematical knowledge, a cultural knowledge that allows him to be opened to the knowledge of other areas that not his specific area, and so to acquire knowledge about the world history, the development of sciences and of the society